2021
DOI: 10.3389/fphy.2021.785885
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis of the Transmission Route for the African Swine Fever Virus in Mainland China

Abstract: African swine fever first broke out in mainland China in August 2018 and has caused a substantial loss to China’s pig industry. Numerous investigations have confirmed that trades and movements of infected pigs and pork products, feeding pigs with contaminative swills, employees, and vehicles carrying the virus are the main transmission routes of the African swine fever virus (ASFV) in mainland China. However, which transmission route is more risky and what is the specific transmission map are still not clear e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Feed and transport vehicles were linked to transmission of porcine epidemic diarrhea virus [83][84][85]. Also, transportation of pigs was considered as a potential transmission route for African swine fever virus [86]. An experimental model showed that contaminated trailers can be a source of transmission of porcine reproductive and respiratory syndrome virus [87].…”
Section: Discussionmentioning
confidence: 99%
“…Feed and transport vehicles were linked to transmission of porcine epidemic diarrhea virus [83][84][85]. Also, transportation of pigs was considered as a potential transmission route for African swine fever virus [86]. An experimental model showed that contaminated trailers can be a source of transmission of porcine reproductive and respiratory syndrome virus [87].…”
Section: Discussionmentioning
confidence: 99%
“…[ 51 ]) 2017 mechanistic spatial structure and transmission, limited data yes cattle Italy hypothetical highly contagious livestock holdings livestock movement, personnel static LITS 8 (Hu et al . [ 52 ]) 2021 mechanistic spatial limited data yes pigs China African swine fever livestock holdings, slaughter point livestock movement static LITS 9 (Wiltshire [ 53 ]; [RUSHPNBM]) (Bucini et al . [ 54 ]; Koliba et al .…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, nodes or edges were sometimes added or removed by copying empirical records exactly (i.e. without modelling these) [ 44 , 52 ]. Contrastingly, eight ABMs and two statistical models generated dynamically evolving networks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three recognized factors influence ASF occurrence: the host, the landscape, and the factors related to human activities [ 10 ]. Out of Africa, swill-feeding and pig/pork transport are considered the main transmission routes, whereas direct contact between infected and non-infected animals has a limited role in long-distance transmission [ 11 ].…”
Section: Introductionmentioning
confidence: 99%